Effectiveness of Gelatin Extracted from Chicken Claws as A Natural Preservatives for Beef and Fish - Ganjar Fadilah; Pramudita Putri Kusuma; Teguh Endah Saraswati (ALCHEMY Jurnal Penelitian Kimia, 2014)
Gelatin  has  been  successfully  extracted  from  chicken  clawsby  acid  hydrolysis method through four major stages of degreasing, demineralization, extraction and drying. The yield of  extracted  gelatin obtained  from wet chicken claws  was about 6.21  %  (w/w). The  effectiveness  of  gelatin  as  preservative  applied  in  beef  and  fish  was  physically, chemically and microbiologically  studied  by  organoleptic  analysis,  peroxide test, bacteria inhibition  test  and  number  calculation, respectively. Organoleptic analysis by hedonic  test shows  there  were significant  differences  for  color  and  texture  parameters  between  gelatin coated  samples  and control  samples  at  concentrations  of  1:1  (w/w).  Peroxide number analysis  by  iodometry  indicates  the  use  of  gelatin  in  the  preservation  of  meat  and  fish decreased the oxidation number. The result of inhibition test againts Staphylococcus aureus bacteria  shows  the  gelatin  concentration  of  20  %  provided  greatest  halo  zone  diameter (inhibitory  region)  as  19.44  ±  2.11  mm. The colony bacteria test shows the use of gelatin potentially  inhibited  the growth  of  bacteria  up to  75  %.  Overall,  the results  conclude  that gelatin  extracted from chicken claws  has the potential  activities  as a  natural preservative for beef and fish.